PRAKTEK PEMBIAYAAN MUSYARAKAH PADA LEMBAGA KEUANGAN SYARI’AH - Wahyuni, Nur (LIPI, 2019)
The purpose of this research 1) Agreement on the financing musyarokah BMT is an agreement that they use in accordance with the principles of sharia is based on the Al-Quran and Al-Hadith. The parties have an equal footing, and have equal rights and obligations. Agreement was also conducted to establish the benefit through the provision of capital to partners in need of funds and does not contain elements of entrapment. 2) The division of profits in accordance with the existing literature, defined as the portion of the contract executed, between the customer and BMT nobody feels aggrieved because there is already an agreement in advance. In the division of profits each month the customer must be reported and paid to the BMT, according to the results obtained without any engineering. 3) The performance of the partners has not looked good, a lot of customers with problems. So that BMT can not be known in both the level of empowerment and its outcome. Problems of the partners can be handled by giving authority to the other partners in managing the assets need to pay attention to the difficulties of negligence and both intentional and partner unintentionally. Partners must be competent in providing or given legal powers.